Mitochondrial ATP Depletion Disrupts Caco-2 Monolayer Integrity and Internalizes Claudin 7 - JanssenDuijghuijsen, Lonneke M.; Grefte, Sander; de Boer, Vincent C. J.; Zeper, Lara; van Dartel, Dorien A. M.; van der Stelt, Inge; Bekkenkamp-Grovenstein, Melissa; van Norren, Klaske; Wichers, Harry J.; Keijer, Jaap (Frontiers in Physiology, 2017)
Objective:In vivo studies suggest that intestinal barrier integrity is dependent on mitochondrial ATP production. Here, we aim to provide mechanistic support, using an in vitro model mimicking the oxidative in vivo situation. Methods: Human Caco-2 cells were cultured for 10 days in culture flasks or for 14 days on transwell inserts in either glucose-containing or galactose-containing medium. Mitochondria were visualized and cellular respiration and levels of oxidative phosphorylation (OXPHOS) proteins were determined. Mitochondrial ATP depletion was induced using CCCP, rotenone, or piericidin A (PA). Monolayer permeability was assessed using transepithelial electrical resistance (TEER) and fluorescein flux. Gene expression and cellular distribution of tight junction proteins were analyzed. Results: Caco-2 cells cultured in galactose-containing, but not in glucose-containing, medium showed increased mitochondrial connectivity, oxygen consumption rates and levels of OXPHOS proteins. Inhibition of mitochondrial ATP production using CCCP, rotenone or PA resulted in a dose-dependent increase in Caco-2 monolayer permeability. In-depth studies with PA showed a six fold decrease in cellular ATP and revealed increased gene expression of tight junction proteins (TJP) 1 and 2, occludin, and claudin 1, but decreased gene expression of claudin 2 and 7. Of these, claudin 7 was clearly redistributed from the cellular membrane into the cytoplasm, while the others were not (TJP1, occludin) or slightly (claudin 2, actin) affected. In vivo studies suggest that intestinal barrier integrity is dependent on mitochondrial ATP production. Here, we aim to provide mechanistic support, using an in vitro model mimicking the oxidative in vivo situation. Conclusions: Well-functioning mitochondria are essential for maintaining cellular energy status and monolayer integrity of galactose grown Caco-2 cells. Energy depletion-induced Caco-2 monolayer permeability may be facilitated by changes in the distribution of claudin 7.